Expression of STEAP1 and STEAP1B in prostate cell lines, and the putative regulation of STEAP1 by post-transcriptional and post-translational mechanisms - Gomes, Inês (2014)
STEAP1 gene is overexpressed in several kinds of tumors, particularly in prostate cancer. Besides STEAP1, there is another related gene, STEAP1B, which may encode two different transcripts. Although several studies have been pointing STEAP1 as a putative immunotherapeutic target and biomarker, the mechanisms underlying its regulation are not fully understood. In silico analysis allowed us to show that STEAP1 and STEAP1B share high homology, but with slight differences at structural level. Experiments with prostate cells showed that STEAP1B2 is overexpressed in cancer cells. Regarding STEAP1 regulation, it is demonstrated that the stability of mRNA and protein is higher in LNCaP than in PNT1A cells. Of note, serum triggered opposite effects in LNCaP and PNT1A in relation to STEAP1 stability, e.g., increasing it in PNT1A and decreasing in LNCaP. These results suggest that STEAP1 may be regulated by post-transcriptional and post-translational modifications (PTM), which may differ between non-neoplastic and neoplastic cells. These PTM are supported through in silico analysis, where several modifications such as N-glycosylation, N-Glycation, Phosphorylation and O-linked β-N-acetylglucosamine, may occur in STEAP1 protein. In conclusion, these data indicate that STEAP1B2 is overexpressed in neoplastic cells, and PTM may be involved in regulation of STEAP1 expression in prostate cells.